Logistics Optimisation of Oil Palm Fronds at Plantations for Energy Conversion - Nur Athira Arshad; Afşin Güngör; Shaharin Anwar Sulaiman (Platform, a Journal of Engineering)
Oil palm frond (OPF) is a form of clean energy with a strong potential to generate electricity due to its abundance and consistent availability throughout the year. However, the pruned OPF is usually laid scattered on the ground throughout the vast areas of palm oil plantations. The logistics of handling pruned OPF pose a low efficiency of the supply chain system and may involve high delivery costs due to key factors such as high transportation cost of a low bulk density material and high labour cost. The optimal way of handling biomass prior to utilisation in a gasification plant remains unclear in terms of ensuring an economical and sustainable ecosystem. The objective of this work is to study the OPF supply chain system by optimising the method of collecting the scattered OPF biomass, the type of equipment used, as well as the transportation used to transfer the feedstock to the power plant built at the lowest cost. Five different OPF supply chain systems are considered. Their configurations are analysed through economic analysis and sensitivity analysis. It was found that the system that involved chipping activity at the plantation and centralised drying at the power plant would result in the lowest delivery cost of RM70 per tonne.